A periosteum-derived cell line to study the role of BMP/TGFβ signaling in periosteal cell behavior and function - Moore, Emily R.; Maridas, David E.; Gamer, Laura; Chen, Gavin; Burton, Kathryn; Rosen, Vicki (Frontiers in Physiology, 2023)
The periosteum is a thin tissue surrounding each skeletal element that contains stem and progenitor cells involved in bone development, postnatal appositional bone growth, load-induced bone formation, and fracture repair. BMP and TGFb signaling are important for periosteal activity and periosteal cell behavior, but thorough examination of the influence of these pathways on specific cell populations resident in the periosteum is lacking due to limitations associated with primary periosteal cell isolations and in vitro experiments. Here we describe the generation of a novel periosteumderived clonal cell (PDC) line from postnatal day 14 mice and use it to examine periosteal cell behavior in vitro. PDCs exhibit key characteristics of periosteal cells observed during skeletal development, maintenance, and bone repair. Specifically, PDCs express established periosteal markers, can be expanded in culture, demonstrate the ability to differentiate into chondrocytes, osteoblasts, and adipocytes, and exhibit an osteogenic response to physical stimulation. PDCs also engage in BMP and/or TGFb signaling when treated with the activating ligands BMP2 and TGFb-1, and in response to mechanical stimulation via fluid shear. We believe that this PDC line will be useful for large-scale, long-term experiments that were not feasible when using primary periosteal cells. Anticipated future uses include advancing our understanding of the signaling interactions that occur during appositional bone growth and fracture repair and developing drug screening platforms to discover novel growth and fracture healing factors.